Osteonecrosis in children with acute lymphoblastic leukemia - Kunstreich, Marina (Haematologica, 2016)
The morbidity and toxicity associated with current intensive treatment protocols for acute lymphoblastic leukemia in childhood become even more important as the vast majority of children can be cured and become long-term survivors. Osteonecrosis is one of the most common therapy-related and debilitating side effects of anti-leukemic treatment and can adversely affect long-term quality of life. Incidence and risk factors vary substantially between study groups and therapeutic regimens. We therefore analyzed 22 clinical trials of childhood acute lymphoblastic leukemia in terms of osteonecrosis incidence and risk factors. Adolescent age is the most significant risk factor, with patients >10 years old at the highest risk. Uncritical modification or even significant reduction of glucocorticoid dosage cannot be recommended at this stage. A novel and innovative approach to reduce osteonecrosis-associated morbidity might be systematic early screening for osteonecrosis by serial magnetic resonance images. However, discriminating patients at risk of functional impairment and debilitating progressive joint disease from asymptomatic patients still remains challenging.